Development of Ciprofloxacin-loaded PCL-PEG Hydrogels - Ismail, Mohamad Wafiuddin; Ahmad Shariff, Siti Hajar; Haris @ Harith, Muhammad Salahuddin (Universiti Putra Malaysia, 2022)
The incorporation of polymer blending into hydrogel formulation is expected to improve the drug loading and encapsulation efficiency of the hydrogel for skin application. Star-shaped polymer made up of poly(caprolactone)-b-poly(ethylene glycol) (PCL-b-PEG) has a great potential to be used as polymer blending in the hydrogel formulation as the PCL region can increase drug encapsulation through hydrophobic-hydrophobic interaction with the hydrophobic drug, and the PEG region can increase the solubility of the polymer to be used as a drug cargo in human body. In this study, two hydrogel formulations will be incorporated with 4-arm star-shaped PCL-b-PEG (4s PCL-b-PEG) to demonstrate drug loading percentage and drug encapsulation efficiency between the two formulations. The key ingredients of the hydrogel consist of the synthesized star-shaped PCL-b-PEG polymers as the drug cargo, along with Carbopol 940 as the gelling agent, ciprofloxacin as the hydrophobic drug model, methyl and propyl paraben as the preservative, trifluoroethanol, triethanolamine and water. The drug loading and encapsulation efficiency of both formulations were found to be more than 99%, indicating high capability of the formulations as hydrophobic drug cargo.